Análise da relação entre a cultura organizacional e o ambiente propício ao desenvolvimento de inovações: estudo em uma instituição de ensino - Souza, Luiz Fernando de (2019)
An institution that analyzes your organizational culture as a facilitator for innovation development can make it a valuable factor for achieving your goals and fulfilling your social function. Organizational culture is an important factor for making changes in institutions by encouraging innovative and entrepreneurial behaviors. Innovation within educational institutions is highly demanded because it is inserted in a society in constant transformation and through it there is the insertion of the citizen in their work environment. Creating an environment that favors innovation is complex, since it goes far beyond the availability of material or financial resources, it is important that the staff members of the institution have this practice internalized and develop them naturally in the performance of their activities. Thus, the general objective of this study is to analyze the relationship between organizational culture and the environment conducive to the development of innovations, with the object of study an educational institution. To analyze this relationship, the model proposed by Machado and Carvalho (2013) was used, which interrelate the organizational culture with the environment conducive to the development of innovations. Thus, in order to meet the general objective of this research, it was decided to conduct a quantitative approach study, defined as the objectives as descriptive, cross-sectional, and survey method. Data treatments were performed through descriptive analysis to characterize the institution to which the sample was composed and to verify the distribution of data for each research construct, using frequency analysis. Subsequently, Cronbach's Alpha reliability, Composite Reliability and Extracted Average Variance tests were performed and the adjusted model considering the indices proposed in the literature. Finally, Structural Equation Modeling was performed using the SPSS software with the AMOS extension, in order to verify the relationship between the model constructs and to test the hypotheses. As a result, the research showed that the servants perceive that the Institution's culture is more collectivist than individualistic and with a short distance from power. They also noticed the presence of the results, processes, leadership, autonomy, internal relationship of the innovation group, dependence, formalization and effectiveness in the relationship as present in the favorable environment for the development of innovations, thus verifying that the model used including the dimensions of innovation and innovation. The dimensions related to culture organization is adherent. The results show a positive relationship between the research constructs, except regarding the relationship between the Organizational Culture group and the External Dimensions of the innovation groups on the Results.